The so-called role-responsibility and the law - Peno, Michał (Acta Universitatis Lodziensis. Folia Iuridica, 2015)
Responsibility is a “core issue” in philosophy of law. “Responsibility” in a legal discourse refers primarily to formal sanctions or it expresses an idea of having to answer for something. I argue in the study that the legal responsibility can be attached to social roles (or even tasks), which are important to the functioning of the society. I try to elucidate the notions of a role (social role) and role-responsibility. This analysis leads to the conclusion that the role responsibility (the notion of the role-responsibility is derived from the Herbert Hart’s philosophical works) is largely constituted by inter-connected sets of rights, duties and responsibilities. Moreover, the role responsibility plays an important role in the law.